The effect of agomelatine and melatonin on sleep-related eating: a case report - Zapp, Angela Alexandra; Fischer, Eva Caroline; Deuschle, Michael (Journal of medical case reports, 2017)
Sleep-related eating may occur in the context of mental illness, sleep disorders, or psychopharmacological treatment. Frequently, sleep-related eating leads to severe weight gain and, so far, there are no treatment options for the condition.